冲突与融合 ：试论黄锦树小说中的马来西亚华巫关系描写 = Conflict and integration : an analysis of Ng Kim Chew’s representation of the Chinese-Malay relationship in Malaysia - 陈彦如 Tan, Yan Ru (2014)
华人在马来西亚占全国人口约四分之一比例，是仅少于马来人的第二大族群。由于巫统政府长期实行以马来人为优先的族群政策，间接打压华人的地位，华巫之间的冲突与矛盾不断渗透社会各个阶层。在长期对立的氛围下，马来西亚华人也往往对马来人抱持愤懑不平的情绪。然而，随着全球化的趋势政府逐步推行了更多元化的政策，华巫之间的关系也得以随之改善。在此复杂的冲突与融合的环境背景下，许多马来西亚华人作家更是在作品当中表现出各个民族（尤以华人和马来人为主）间的互动关系。其中，马华文学作家黄锦树在其小说中不做刻意的掩藏、甚至毫不保留地刻画华巫之间的关系。由此，本文将针对黄锦树小说中描写的华巫关系进行分析，探索华巫形象及互动塑造背后的文化含义以及作者所欲表达的社会现实。通过小说所再现的华巫冲突与融合，本文将进而分析黄锦树对两族关系描写的转变。The Chinese in Malaysia often feel oppressed as the Malaysian government placed priority on the Malay ethnic group when implementing national policies. This resulted in a long-term conflict and tension between the two ethnic groups. However, with globalization and the Malaysian government’s efforts to establish multi-cultural policies, the Chinese-Malay relationship improved over the years. With such elasticity in tension and harmony within the society, many Malaysian Chinese writers have since written about the delicate interactions amongst various ethnic groups (mainly between the Malays and Chinese). Amongst them, Ng Kim Chew’s novels stand out with its graphic and detailed representation of the Chinese-Malay relationship. As such, this paper seeks to analyze these representations and explore the cultural annotations and projected social reality behind them, and to examine the change in Ng’s perspective on the Chinese-Malay relationship in Malaysia.